Running Water in Clarice Lispector's The Besieged City - Johnny Lorenz (Latin American Literary Review, 2021)
When, in Clarice Lispector's The Besieged City (1949), our protagonist, Lucrécia, contemplates her relationship with the city of São Geraldo, she pays special attention to water and water infrastructure. Pipes and embankments and viaducts, even the humble faucet – all of this technology of controlling and delivering water becomes a way of conceptualizing the city, but waterworks, I argue, is also an integral part of the text's experiment with vision. Can one see what is there? Can one see the "thing" liberated from our vocabularies? In Chapter 6, in which, supposedly, nothing is happening, Lucrécia is at the faucet, doing the dishes, losing her sense of self as she communes with the city. Later, when she notices a broken faucet in the storeroom, she confronts the thingness of this piece of equipment. To realize the thingness of herself is her most powerful desire. My analysis attempts to complicate feminist readings of The Besieged City by arguing that the text imagines objectification not as a problem, but as a paradoxical attempt at agency. Previous readings approach Lispector's novel as a condemnation of the city; my analysis understands The Besieged City as a representation of the modern sublime.